Neglected Water, Sanitation and Hygiene Aspects in Preventing Childhood Stunting - Dwipayanti, Ni Made Utami; Purnama, Sang Gede (Public Health and Preventive Medicine Archive, 2022)
Approximately 165 million (25,7%) children globally experience chronic malnutrition or stunting.1 In Indonesia, 29.6% of children under five are recorded as short and very short.2 The stunting prevention framework underlines that stunting prevention needs to be carried out with a comprehensive approach targeting specific nutritional factors such as the adolescents’ and young couples’ health, pregnancy supplements, exclusive breastfeeding, child feeding, as well as sensitive nutritional factors such as food security, mental health during pregnancy, women empowerment, access to clean water and sanitation, and family health services.1